HEMORRHAGIC STROKE AS POST-INTRACEREBRAL HEMORRHAGE INFLAMMATION - Yabluchanskiy, A. М. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Intracerebral hemorrhage remains one of the less studied problems in modern neurology. Later publications suggest that inflammatory processes play a significant role in hemorrhagic stroke; however, most of these reports represent fragmentary information on the local and less system levels of inflammation, and do not show the correlation between these levels. In this review the attention is focused on the compensatory, adaptive and restorative nature of the inflammation in the post-intracerebral hemorrhage damage. Non-complicated and complicated forms of inflammation are discussed regarding their influence on the course and outcomes of hemorrhagic stroke. Optimization of complicated inflammation could be one of the approaches for improving the outcomes of hemorrhagic stroke.